Ukrainian Existential Anxiety Questionnaire (EAQ) Adaptation for Adolescents - Kryazh, Iryna; Logvinenko, Iryna (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2026)
This article presents the results of developing and validating a Ukrainian-language adaptation of the existential anxiety questionnaire (EAQ) for adolescents. The sample included 141 students in grades 10-11, aged 14-17 (M = 15.8 years, SD = 0.71, 85 girls and 56 boys). An analysis of the questionnaire factor structure revealed that inverse statements, which refer to the absence of guilt, trust in fate, and the absence of doubts about previous meanings of life, interfere with the diagnosis of existential anxiety. A shortened 7-item questionnaire is proposed, which includes six statements describing three types of existential anxiety manifestations, along with a statement about belief in the meaning of life in general. Empirical grounds for considering existential anxiety as a single-factor construct are provided. The internal consistency (ω = 0.76) of the abbreviated Ukrainian-language version of the Existential Anxiety Questionnaire for Adolescents (EAQ-UA) was confirmed. Moderate positive correlations of existential anxiety with the Beck Anxiety Inventory and eco-anxiety scores, as well as a weaker negative correlation with life satisfaction and a positive correlation with negative experiences, support convergent validity. The absence of a significant correlation with positive experiences and a weak correlation with rumination support the discriminant validity of the abbreviated version of the EAQ-UA.